Uromodulin Triggers IL-1β–Dependent Innate Immunity via the NLRP3 Inflammasome - Darisipudi, Murthy Narayana (American Society of Nephrology, 2012)
Uromodulin/Tamm-Horsfall protein is not immunostimulatory in the tubular lumen, but through unknown mechanisms it can activate dendritic cells and promote inflammation in the renal interstitium. Here, we noted that uromodulin isolated from human urine aggregates to large, irregular clumps with a crystal-like ultrastructure. These uromodulin nanoparticles activated isolated human monocytes to express costimulatory molecules and to secrete the mature proinflammatory cytokines, including IL-1β. Full release of IL-1β in response to uromodulin depended on priming of pro-IL-1β expression by Toll-like receptors, TNF-α, or IL-1α. In addition, uromodulin-induced secretion of mature IL-1β depended on the NLRP3 inflammasome, its linker molecule ASC, and pro-IL-1β cleavage by caspase-1. Activation of NLRP3 required phagocytosis of uromodulin particles into lysosomes, cathepsin leakage, oxidative stress, and potassium efflux from the cell. Taken together, these data suggest that uromodulin is a NLRP3 agonist handled by antigen-presenting cells as an immunostimulatory nanoparticle. Thus, in the presence of tubular damage that exposes the renal interstitium, uromodulin becomes an endogenous danger signal. The inability of renal parenchymal cells to secrete IL-1β may explain why uromodulin remains immunologically inert inside the luminal compartment of the urinary tract.